Designing Chemistry Teaching Materials and Worksheets to Promote Students' Creative Thinking Skills: A Systematic Literature Review - Irawan, Nisrina Zahira Putri; Anwar*, Sjaeful; Munawaroh, Heli Siti Halimatul (Universitas Syiah Kuala, 2024)
This study investigated the strategy of designing chemistry teaching materials and worksheets to promote creative thinking skills. This study conducts a systematic literature review method. Data collection is conducted from 573 articles in semantic scholar databases based on inclusion criteria. The articles used in this study are 27 articles selected for review. Based on the systematic literature review results, there are three findings related to strategies for designing teaching materials and chemistry worksheets to promote students' creative thinking skills, including 1) Inserting real-world problems or contexts in teaching materials; 2) Designing materials based on the results of needs analysis, indicators of chemistry learning outcomes from the applicable curriculum, the structure of teaching materials or worksheets, and based on indicators or aspects of creative thinking skills; 3) Designing chemistry teaching materials and worksheets based on aspects of the learning approach and syntax of the learning model used. The development of chemistry teaching materials and worksheets to promote students' creative thinking skills can be further researched using the fuzzy delphi method and a systematic and detailed method of developing teaching materials, including three levels of representation in conveying chemical concepts so the creativity skills can be developed